Evaluation of field compaction of a filtered residue from alumina production - Nery, KD; Villar, LFS; Moreno, RA; Freire Neto, JP; Scarmínio, M; Junior, RS (Paste 2013: Proceedings of the 16th International Seminar on Paste and Thickened Tailings, 2013)
Filtration technology has been applied to dewater industrial residue from alumina production to reduce final volume and to provide safer disposal. This is important due the decrease of licensed areas for waste storage and the proximity of populated regions to these areas. Filtering residue using a filter press results in dry material with about 70 to 80% solid content, called ‘dry cake’. It has a high density when it is intact, but it breaks into small pieces, forming loose material, when it comes out of the filter chamber. Thus, to reduce the volume of the waste material, it is necessary to compact it. Since it is an unusual material, there is little information available about its behaviour during and after compaction. The layer thickness, the right equipment to be used for compaction and all possible methods to be applied in this process have to be studied to assure that the desired densities will be reached to obtain a safe storage system. Also, the process must be efficient and have low operating costs. This paper presents an evaluation of the field behaviour of a filtered residue from alumina production after compaction. A field test area was constructed, where the filtered residue was compacted and its behaviour and the feasibility of its deposition in this manner were evaluated. The testing method was adjusted according to the amount of material available for the tests. Before compaction of the dry residue, a pile was formed just by dumping it, without compaction, and the density and angle of repose of the pile were measured. The compaction of the residue was carried out using a tracked excavator and the densities were measured after each pass over the residue. A Standard Proctor test was also performed to compare the densities achieved in the lab and in the field. The tests proved the method is quite promising in terms of gain in density, and therefore increased disposal capacity, since the final waste volume was reduced.